(untitled) (Experimental biology, 2025)
This paper deals with the origin and evolution of the genus Populus L. (poplar) from the family Salicaceae, with emphasis on species distributed in natural conditions of Western Kazakhstan. Paleobotanical, morphological and ecological data were analyzed, allowing to trace the ways of formation and adaptation of different poplar species in conditions of steppe and semi-desert ecosystems. Hybridization, introgression and plastid capture are characteristic phenomena in the evolution of Populus. Studies of the phylogeny of the genus confirm the existence of extensive gene flow between geographically close species, even those belonging to different sections, if they are not reproductively isolated. This fact should be taken into account in phylogenetic reconstructions, avoiding the erroneous use of interspecific introgression as a sign of relatedness. The work emphasizes the importance of the genus Populus as a bioindicator of climatic changes and as a promising object for forest ameliorative and landscape works.